2020
DOI: 10.1155/2020/4168420
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationships between Multiple Endocrine Hormones and Return of Spontaneous Circulation (ROSC) in Cardiac Arrest Patients: Possible Association of the Serum Free T4 Level with ROSC

Abstract: Background. Endocrine hormones are closely associated with homeostasis, so it is important to clarify hormone secretion dynamics in shock. Few reports, however, have examined the dynamics of endogenous hormone secretion relative to prognosis in cardiac arrest patients. Therefore, to clarify the roles of endocrine hormones in out-of-hospital cardiac arrest (OHCA) patients, the concentrations of anterior pituitary, thyroid, and adrenocortical hormones were measured, and their associations with return of spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As for the metabolic analysis of I/R, the GAT1 group had a lower level of acidosis and base intake than the CG group, suggesting that the combination of adrenaline and candesartan can protect myocardial tissue and improve energy metabolism after ROSC. Since candesartan is one of the most potent aldosterone suppressors and higher potassium levels are implicated in lower ROSC rates, we expected higher potassium levels on GAT1 48 50 . However, potassium levels were lower 10 min after ROSC.…”
Section: Discussionmentioning
confidence: 95%
“…As for the metabolic analysis of I/R, the GAT1 group had a lower level of acidosis and base intake than the CG group, suggesting that the combination of adrenaline and candesartan can protect myocardial tissue and improve energy metabolism after ROSC. Since candesartan is one of the most potent aldosterone suppressors and higher potassium levels are implicated in lower ROSC rates, we expected higher potassium levels on GAT1 48 50 . However, potassium levels were lower 10 min after ROSC.…”
Section: Discussionmentioning
confidence: 95%
“…The search strategy identified a total of 11,834 records, of which 6914 were non‐duplicates. After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 11–128 …”
Section: Resultsmentioning
confidence: 99%
“…After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 . 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…[9] World J Emerg Med, Vol 14, No 2, 2023 Factors that predict ROSC and long-term survival in patients with OHCA have been studied, including prehospital information, such as age, sex, witnesses, bystander cardiopulmonary resuscitation (CPR), cause leading to cardiac arrest, and initial rhythm. [10] According to blood tests, various factors, such as levels of K + , [11,12] Na + , [13] blood glucose, [13] ammonia, [14] brain natriuretic peptide, [15] lactate, [16][17][18] and free thyroxine 4, [19] have been reported to affect the prognosis of OHCA. Moreover, significant activation of coagulation occurs as a part of the pathogenesis after cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%